Long-run trends and recent developments in official assistance from donor countries - Howard White (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Official flows account for close to half of capital flows to developing countries, and close to 90 per cent of receipts for Sub-Saharan Africa. This paper documents trends in these official flows over the last three decades. The most striking trend has been declining aid volume. Following two decades of relative stability, official flows have decline in the 1990s; in particular aid to just 0.2 per cent of donor GNP. A second trend is the decline in aid to low-income countries, partly as aid flows are diverted to transition economies and `trouble spots'. As a result of these trends, real aid per capita to Sub-Saharan Africa fell by 40 per cent in the 1990s. Continuing an existing trend, multilateral agencies have accounted for a growing share of total aid, in part as a result of the expansion of EU aid, but non-EU donors have contributed more of their aid through the UN system. Positive developments have been the increased concessionality of aid and a move toward untying. However, substantial parts of the multilateral system, notably the World Bank, continue to extend loans rather than grants. And the move to untying is not well-established, having been somewhat reversed in some countries in recent years. Finally, the aid programme of most donors is thinly spread over many recipients. Whilst there are good grounds to question the current fashion for selectivity, there remain good developmental arguments for greater concentration by individual donors.
Keywords: F34; F35; O19; 330; development aid; bilateral aid; multilateral aid; Entwicklungshilfe; Entwicklungskooperation